Brachybacterium massiliense sp. nov., a new bacterium isolated from stool from a healthy Senegalese child. (September 2019) - Mekhalif, F.; Tidjani Alou, M.; Zgheib, R.; Lo, C.I.; Fournier, P.-E.; Raoult, D.; Lagier, J.-C.
Abstract: Based on our phenotypic and genotypic analyses, Brachybacterium massiliense strain Marseille-P2240 T (= CSURP2240; = DSM 101766) is a new species isolated from stool of a healthy subject. The strain was stained Gram-positive. It was aerobic, catalase-positive and oxidase-negative. Its optimal growth occurs at 37°C in aerobic condition. The 16S ribosomal RNA sequence analysis revealed that strain Marseille-P2240T shown 98.18% similarity with Brachybacterium saurashtrense strain JG 06, the more closely related species with standing in nomenclature.